Flavour Characterization Of Jackfruit (Artocarpus Heterophyllus L.) From Five Cultivars And Optimization Of Canning Conditions For Jackfruit Puree - Ong, Bee Tein (2006)
The study concerns flavour characterization of five jackfruit (Artocarpus heterophyllus L.) cultivars and optimization of canned jackfruit puree production. In the first part of this study, twenty three volatile compounds extracted using dichloromethane solvent extraction were tentatively identified by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). As ripening progressed, there was an increase in volatile compound formation. Development of new volatile flavour compounds in trace amounts at day 3 after harvest indicated the start of jackfruit ripening. Data obtained showed that the ripening process of jackfruit was at its optimum at day 5 after harvest. Variation of volatile compounds in different portions (top, middle and bottom) of the fruit during ripening was too little to give any significance. The volatile profiles of jackfruit flavour in five cultivars were established using headspace solid phase microextraction (SPME) and gas chromatography-time of flight mass spectrometry (GC-TOFMS). Qualitative and quantitative analyses were carried out using divinylbenzene/carboxen/polydimethylsiloxane (DVB/CAR/PDMS) fiber with an extraction time of 10 min. Thirty seven compounds were identified from the five cultivars tested. Characteristic aroma which are in higher concentrations and contributed to jackfruit flavour were found to be ethyl isovalerate, 3-methylbutyl acetate, I -butanol, propyl isovalerate, isobutyl isovalerate, 2-methylbutanol, and butyl isovalerate. The consistent occurrence of these compounds in all cultivars of jackfruit suggested their importance in contributing to the sweet and fruity note of jackfruit. Concentration of the volatile compounds present played an important role in determining the overall flavour of each fruit cultivar. Each cultivar also possessed its own unique compound which distinguished them from one to another.